Modern web development with HTML5 and CSS - Andrew, Rachel; Safari eBooks ([Place of publication not identified] : Infinite Skills, 2015)
"In this Modern Web Development with HTML5 and CSS training course, expert author Rachel Andrew will teach you about modern HTML5 and CSS, showing you how to style content and build simple, responsive layouts. This course is designed for the absolute beginner, meaning no prior experience with HTML or CSS is required. You will start by learning the basics of developing for the web, then jump into HTML fundamentals, such as HTML Syntax, the Doctype, links, images, and validation. From there, Rachel teaches you about structural HTML, CSS fundamentals, text and typography, and color and images. This video tutorial also covers how to layout with CSS, forms in HTML and CSS, and HTML5 audio and video. Finally, you will learn about responsive design, as well as browser and device testing and how to fix problems and ensure accessibility."--Resource description page.
Title from resource description page (viewed April 3, 2015).
Presenter, Rachel Andrew.
Keywords: Web sites -- Design; Web site development; HTML (Document markup language); Cascading style sheets; Electronic books